Atmospheric turbidity measurements using a 355NM-532NM lidar and a sunphotometer in Manila, Philippines - Vallar, Edgar A. (Animo Repository, 2011)
Real-time measurements of atmospheric turbidity were conducted in Manila, Philippines using the De La Salle University (DLSU) 355nm-532nm Mie LIDAR and Middleton SP02 4-channel sunphotometer. The DLSU Mie LIDAR system and the Middleton SP02 Sunphotometer are currently housed in the Science & Technology Research Center of DLSU, Manila, Philippines. DLSU is located in the center of Manila and is approximately 900 meters from Manila Bay. The DLSU LIDAR mainly consists of a 20-Hz, Q-Switched Nd:YAG laser and 20-cm diameter, 800-mm focal length Newtonian telescope. The SP02 Sunphotometer is a 1.25-kg commercial 4-channel Sunphotometer with center wavelengths at 368nm, 500nm, 675nm and 862nm (10-nm bandwidth). The sunphotometer was attached to a homemade tracker mount that tracks the sun and gets data automatically throughout the day. DLSU LIDAR researchers built LabView-based VI's for both the LIDAR and the sunphotometer enabling automatic data acquisition and processing. A detailed description of both systems can be found in www.dlsu-lidar.tk. The optical depth was determined from the data of each instrument. The Ångström turbidity law was then utilized to obtain the atmospheric turbidity. Typical values of turbidity vary from 0.0 to 0.5. For clean, clear, turbid and very turbid atmospheres, the turbidity values are 0.0, 0.1, 0.2 and 0.4, respectively. Experiments were conducted last 2010 January 08, 12 and 22. The average turbidity up to 400 meters horizontal range from the LIDAR site was determined. The LIDAR derived turbidity values were 0.184, 0.23, and 0.0295, respectively for the three dates. The corresponding sunphotometer values are 0.191, 0.235, and 0.0280, respectively. The January 08 and 12 values show a turbid atmosphere while the January 22 value indicates a relatively clear atmospheric condition.